Editor's Comments: Bringing in Consumers - Brief, Arthur P.; Bazerman, Max (Academy of Management Review, 2003)
The article argues that businesses have an obligation to provide beneficial products in order to add value to society and satisfy customers. The article explains the benefit of conducting management research with the welfare of the consumer in mind, instead of the welfare of the management. The article argues that consumer research is also more concerned with the management side of the purchasing relationship.